유리섬유 강화 복합재료를 이용한 마찰재 개발에 관한 연구 - 김영운(YOUNG-UN KIM); 최문호(MOON-HO CHOI); 서상하(SANG-HA SEO); 김부안(BU-AHN KIM); 문창권(CHANG-KWON MOON) (Han-guk haeyang gonghak hoeji (Online), 2000)
This study has been investigated to apply fiber reinforced composites instead of asbestos as a friction material. the reinforced used was E-glass fiber and binder resin was phenol having good mechanical properties and heat resistance. And it has been also investigated the effect of molding conditions and some additives such and carbon black, alumina and rubber powder in E-glass fiber/phenol resin composite on the friction on the friction and wear characteristics. As a result, it was found that the molding conditions of E-glass fiber/phenol resin composites for friction materials had to be different from those of phenol resin and was found that the wear rate of E-glass fiber/phenol resin composites added alumina powder was higher than of composites added carbon black in the same wear distance. And it was found that friction coefficient of E-glass/phenol resin composites added carbon black was decreased and that of the composites added the powder of natural rubber and ABS rubber were increased compared to the composites.